Serum Interleukin-34 Levels Are Elevated in Patients with Systemic Lupus Erythematosus - Wang, Hongxu (Molecules, 2016)
Interleukin-34 (IL-34) was initially identified as an alternative ligand for the colony-stimulating factor-1 receptor (CSF-1R) to mediate the biology of mononuclear phagocytic cells. Recently, IL-34 was found to be associated with chronic inflammation, such as in rheumatoid arthritis (RA). Both RA and systemic lupus erythematosus (SLE) are multifactorial autoimmune diseases and are characterized by excessive immune and inflammatory responses. Thus, we investigated whether IL-34 is involved in the pathogenesis of SLE. In all, 78 SLE patients and 53 healthy controls were enrolled in the research. Enzyme-linked immunosorbent assay (ELISA) was employed to measure the concentrations of serological IL-34. Then serum IL-34 levels between the SLE group and healthy controls were analyzed by the Mann-Whitney U test. Meanwhile, the correlations between the serum IL-34 levels and disease activity indexes and other established serum markers were assessed. Furthermore, the serum IL-34 levels of 20 active SLE patients were reevaluated when diseases were in the remission stage from corticosteroids or immunosuppressive drugs. Serum IL-34 levels were significantly higher in SLE patients compared to healthy controls. Their levels were remarkably associated with accumulation of the clinical features of SLE. Additionally, IL-34 titers were positively correlated with the SLE disease activity indexes, anti-double-stranded DNA antibody (anti-dsDNA) titers and C-reactive protein (CRP) levels, and inversely with complement3 (C3) levels. Moreover, serum IL-34 levels were significantly decreased after successful treatment of SLE. Serum IL-34 could be a candidate biomarker for SLE as there are elevated serum levels in treatment-naive SLE patients and we saw a significant decrease after effective treatment.